(untitled) (Pragyaratna प्रज्ञारत्न, 2024)
Senior citizens get encouraged by social media to engage in local community centered events so as to feel less isolated and connected. In Nepal, the number of old people is increasing very fast. The studies objectives to assess how effective social media is in mitigating the issue of serious loneliness among senior citizen. A descriptive cross-sectional survey research design was used, employing a structured questionnaire. The sample included 121 elderly citizens. As they were drawn upon to gather quantitative data: In social media use frequency an increase of one unit would decrease loneliness by 0.35 units strongly related to this also, In fact, Increased perceived social support decreased loneliness by 0.50 units thereby depicting a strong negative correlation, younger individuals have been found to be more prone to being alone than older. The conclusion from that social media was shown to reduce depression among the elderly. Additionally, according to findings, there is need for the elimination of technical barriers as well as creation of digital support networks in order to enhance wellbeing for the elderly.